2021
DOI: 10.1038/s41598-021-89346-6
|View full text |Cite
|
Sign up to set email alerts
|

The impact of atmospheric oxidation on hygroscopicity and cloud droplet activation of inorganic sea spray aerosol

Abstract: Sea spray aerosol (SSA) contributes significantly to natural aerosol particle concentrations globally, in marine areas even dominantly. The potential changes of the omnipresent inorganic fraction of SSA due to atmospheric ageing is largely unexplored. In the atmosphere, SSA may exist as aqueous phase solution droplets or as dried solid or amorphous particles. We demonstrate that ageing of liquid NaCl and artificial sea salt aerosol by exposure to ozone and UV light leads to a substantial decrease in hygroscopi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 79 publications
0
18
0
Order By: Relevance
“…In the model, we considered the gradual compaction and dilution of the chamber volume due to the instrument sampling (see description in the Supplement Sect. S2.1) (Rosati et al, 2021a). The inflow of air from outside the chamber is a likely source for the particle contamination (nitrate and organics) observed with the high-resolution time-of-flight aerosol mass spectrometer (HR-ToF-AMS) (Rosati et al, 2021b).…”
Section: Smog Chamber Experimentsmentioning
confidence: 99%
“…In the model, we considered the gradual compaction and dilution of the chamber volume due to the instrument sampling (see description in the Supplement Sect. S2.1) (Rosati et al, 2021a). The inflow of air from outside the chamber is a likely source for the particle contamination (nitrate and organics) observed with the high-resolution time-of-flight aerosol mass spectrometer (HR-ToF-AMS) (Rosati et al, 2021b).…”
Section: Smog Chamber Experimentsmentioning
confidence: 99%
“…Our observed trend is in line with the predicted temperature dependence obtained with the Arrhenius expression used in the Master Chemical Mechanism version 3.3.1 (MCMv3.3.1) andHoffmann et al (2016), delineating slower reaction rates at colder temperatures. The decay of the concentration of DMS over time for similar experiments at 293 and 273 K, dry and humid conditions, was formerly presented inRosati et al (2021b) and Wollesen deJonge et al (2021). Wollesen deJonge et al (2021) found good agreement between measured and modelled decay rates using the ADCHAM box model.Nucleation and growth rates are known to be inherently dependent on temperature and RH(Seinfeld and Pandis, 2016).…”
mentioning
confidence: 77%
“…Berg et al, 1998;Nilsson et al, 2001;Lewis and Schwartz, 2004;Swietlicki et al, 2008;Modini et al, 2010;Fuentes et al, 2011) and ability to serve as CCN (e.g. Covert et al, 1998;Ovadnevaite et al, 2011;King et al, 2012;Prather et al, 2013;Collins et al, 2013Collins et al, , 2016Nguyen et al, 2017;Fossum et al, 2018;Rosati et al, 2021b) of marine aerosols and, in particular, sea spray aerosols have been studied intensively. Few studies have addressed the water uptake behaviour of secondary DMS-derived aerosols.…”
Section: Introductionmentioning
confidence: 99%
“…8 The composition of SSA, especially the sea salt component, impacts its ability to serve as cloud droplets due to the hygroscopicity of these chemical components. 9 It is important to understand the processes that control SSA production and composition because of its significant role in Earth's radiative budget. 10 SSA is produced via physical ejection of sea spray droplets produced by bubble-bursting.…”
Section: Introductionmentioning
confidence: 99%
“…Atmospheric aerosol plays a critical role in Earth’s radiative budget but remains the single largest source of uncertainty in models estimating potential changes in radiative forcing. , The atmospheric impacts of particles are dependent upon multiple factors including the composition, size, and number concentration, which can all affect their ability to serve as cloud condensation nuclei (CCNs). Sea spray aerosols (SSA) are an important contributor to the total aerosol mass globally. , SSA can be activated into cloud droplets, which have been shown to potentially change the albedo of marine boundary layer clouds by as much as 30% . The composition of SSA, especially the sea salt component, impacts its ability to serve as cloud droplets due to the hygroscopicity of these chemical components . It is important to understand the processes that control SSA production and composition because of its significant role in Earth’s radiative budget …”
Section: Introductionmentioning
confidence: 99%